A re-examination of the expected years of schooling: What can it tell us? - José Irineu Rangel Rigotti; Diana Oya Sawyer; Laetícia Rodrigues de Souza; Clarissa Guimar\~aes Rodrigues (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
EYS is an important component of HDI rankings by country, since the higher its values, the higher a given country is ranked given the other components. However, in its current formulation it only takes into account enrolment rates, and overlooks the progression structure in the school system. Thus, if the indicator is intended to be a proxy for the knowledge accumulated in schools (Hanushek, 2013; Barakat, 2012; Rios-Neto and Guimaraes, 2010), which the HDI's education dimension seeks to represent, results may be misleading, since the structure of school progression is not taken into consideration. This article proposes adjustments to the indicator, to bring it closer to the meaning of schooling, assuming that completion of successive school years can be considered an approximation of greater or lesser education. In addition to age and rate of enrolment, the adjustment also takes into consideration a third component, which is the grade of enrolment. This adjusted indicator for comparative purposes works better if calculated up to an age compatible with the completion of the last cycle in the school system. For ease of presentation, we shall label the HDI indicator EYS and the indicator adjusted by the contribution of delayed students, proposed here, Adjusted Expected Years of Schooling (AEYS).
Keywords: 330